On the importance of rituals in sport - Paweł Piepiora; Justyna Bagińska; język angielski język angielski; język angielski język angielski (Kazimierz Wielki University, 2022)
In this short article, we took a look at the importance of rituals in sports. First we explained the concepts of religion, creed, superstitions, fallacies and rituals. Then we described superstitious thinking and religiosity in psychological terms and on this basis we referred to rituals in sport. We explained the meaning of rituals in sport based on our own professional experiences with athletes. This article is an introduction for conducting a pilot study.